Species composition and density of fish eggs and larvae in the coastal waters of the South-Central Vietnam - Pham, Quoc Huy; Nguyen, Van Long (Vietnam Journal of Marine Science and Technology, 2022)
Based on species composition and density data of fish egg and larvae in South Central coastal sea areas of Vietnam Sea waters were collected at Cù Lao Cham - Thu Bon river, Ly Son - Tra Bong river - Sa Ky river and Nha Trang - Nha Phu lagoon. Thirty-one fish eggs and larvae families were identified (about 18% of total fish eggs and 100% of wholte larvae). Cu Lao Cham - Thu Bon river has the richest species composition as 18 families, following to that is Ly Son - Tra Bong - Sa Ky and lower is Nha Trang - Nha Phu identified 15 and 10 families, respectively. The highest frequency was found in families such as Mullidae, Engraulidae and Synodontidae with 2 to 3 species (groups). The above families account for about 60% of the total number of fish eggs and larvae collected. The average fish eggs and larvae abundance about 3,630 eggs/1,000 m3 of water and 122 larvae/1,000 m3 of water. The highest eggs density is Nha Trang - Nha Phu, and the highest larvae density is Cu Lao Cham - Thu Bon river. Ly Son - Tra Bong - Sa Ky areas have eggs density lower than other areas, especially for larvae density with 22 larvae/1,000 m3 of water.